Influence of resonant plasmonic nanoparticles on optically accessing the valley degree of freedom in 2D semiconductors - Tobias Bucher; Zlata Fedorova; Mostafa Abasifard; Rajeshkumar Mupparapu; Matthias J. Wurdack; Emad Najafidehaghani; Ziyang Gan; Heiko Knopf; Antony George; Falk Eilenberger; Thomas Pertsch; Andrey Turchanin; et al. (Nature Communications)
Abstract The valley degree of freedom in atomically thin transition metal dichalcogenides, coupled with valley-contrasting optical selection rules, holds great potential for future electronic and optoelectronic devices. Resonant optical nanostructures emerge as promising tools for controlling this degree of freedom at the nanoscale. However, their impact on the circular polarization of valley-selective emission remains poorly understood. In our study, we explore a hybrid system where valley-specific emission from a molybdenum disulfide monolayer interacts with a resonant plasmonic nanosphere. Contrary to the simple intuition that a centrosymmetric nanoresonator mostly preserves the degree of circular polarization, our cryogenic experiments reveal significant depolarization of the photoluminescence scattered by the nanoparticle. This striking effect presents an ideal platform for studying the mechanisms governing light-matter interactions in such hybrid systems. Our full-wave numerical analysis provides insights into the key physical mechanisms affecting the polarization response, offering a pathway toward designing novel valleytronic devices.